2013
DOI: 10.1002/jgra.50515
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of medium‐scale traveling ionospheric disturbances observed near the Antarctic Peninsula by HF radar

Abstract: [1] We present a survey of medium-scale traveling ionospheric disturbances (MSTIDs) observed by a Super Dual Auroral Radar Network HF radar located in the Falkland Islands between May 2010 and April 2011. The radar has a field of view that overlooks the Antarctic Peninsula, a known hot spot of gravity wave activity. We present observations of radar ground-backscatter data, in which the signatures of MSTIDs are manifested as structured enhancements in echo power. Observed periods were in the range 30-80 min, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 48 publications
7
65
0
Order By: Relevance
“…Recently, MSTIDs have been studied statistically in many places worldwide using various techniques (Frissell et al 2014(Frissell et al , 2016Fukushima et al 2012;Grocott et al 2013;He et al 2004;Ichihara et al 2013;Ishida et al 2008;Klausner et al 2009;Kotake and Otsuka 2007;Medvedev et al 2013;Oinats et al 2015Oinats et al , 2016Otsuka et al 2011Otsuka et al , 2013Shiokawa et al 2003Shiokawa et al , 2009. In this study, we present observations of MSTIDs' horizontal velocities over Taiwan using HF Doppler sounding.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, MSTIDs have been studied statistically in many places worldwide using various techniques (Frissell et al 2014(Frissell et al , 2016Fukushima et al 2012;Grocott et al 2013;He et al 2004;Ichihara et al 2013;Ishida et al 2008;Klausner et al 2009;Kotake and Otsuka 2007;Medvedev et al 2013;Oinats et al 2015Oinats et al , 2016Otsuka et al 2011Otsuka et al , 2013Shiokawa et al 2003Shiokawa et al , 2009. In this study, we present observations of MSTIDs' horizontal velocities over Taiwan using HF Doppler sounding.…”
Section: Introductionmentioning
confidence: 87%
“…Ishida et al [2008] and Grocott et al [2013] both suggest that midlatitude MSTIDs, such as those observed by BKS, could also be generated in the auroral zone through geomagnetic forcing processes. To search for a possible geomagnetic source, we examined data from a longitudinal chain of magnetometers distributed along the eastern coast of North America through Greenland, as well as a chain in Alaska.…”
Section: Possible Mstid Sourcesmentioning
confidence: 97%
“…Ishida et al [2008] conducted a statistical study using SuperDARN radars in Japan and Alaska which suggested that MSTID propagation from high latitude to midlatitudes is possible. Grocott et al [2013] conducted a more extensive study using the midlatitude, Southern Hemisphere Falkland Islands Radar. They found a correlation (albeit weak) between geomagnetic activity and MSTID occurrence, as well as a preferential equatorward direction of propagation for the majority of MSTIDs observed.…”
Section: 1002/2014ja019870mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of papers presenting statistical studies of TIDs have been published in the last 15 years (Afraimovich et al 1999(Afraimovich et al , 2000Ding et al 2008;Kotake et al 2007;Medvedev et al 2013;Otsuka et al 2011;Shiokawa et al 2003;Tsugawa et al 2004). There are also statistical studies that utilized SuperDARN radar data (Bristow et al 1996;He et al 2004;Ichihara et al 2013;Ishida et al 2008;Grocott et al 2013). Apparently, a relatively small number of such studies are related to the complexity of extensive dataset processing, as well as the issues concerning an automated interpretation of HF radar data.…”
Section: Introductionmentioning
confidence: 99%